Immunoregulation therapy changes the frequency of interleukin (IL)-22+CD4+T cells in systemic lupus erythematosus patients. (9th June 2014) - Zhao, L; Ma, H; Jiang, Z; Jiang, Y; Ma, N
Summary: T cell and T cell-related cytokine abnormalities are involved in the pathogenesis of systemic lupus erythematosus (SLE). Our previous study showed that the interleukin (IL)-22 + CD4 + T cells and IL-22 play an important role in the pathogenesis of SLE. In this study, we aimed to investigate the effects of glucocorticoids (GCs) and immunodepressant agents on IL-22 and IL-22-producing T cell subsets in SLE patients. The frequencies of peripheral blood T helper type 22 (Th22), IL-22 + Th17, IL-22 + Th1 and Th17 cells and the concentrations of serum IL-22, IL-17 and interferon (IFN)-γ in SLE patients receiving 4 weeks of treatment with cyclophosphamide (CYC), methylprednisolone and hydroxychloroquine (HCQ) were characterized by flow cytometry analysis and enzyme-linked immunosorbent assay (ELISA). The frequencies of Th22, IL-22 + Th17 and Th17 cells and the concentrations of IL-22 and IL-17 were reduced in response to the drugs methylprednisolone, cyclophosphamide and hydroxychloroquine for 4 weeks in the majority of SLE patients. However, the percentage of Th1 cells showed no change. No differences in the levels of IL-22 and IL-22 + CD4 + T cells were found between non-responders and health controls either before or after therapy. IL-22 levels were correlated positively with Th22 cells in SLE patients after treatment. These results suggest that elevated IL-22 is correlated with IL-22 + CD4 + T cells, especially Th22 cells, and may have a co-operative or synergetic function in the immunopathogenesis of SLE. GC, CYC and HCQ treatment may regulate the production of IL-22, possibly by correcting the IL-22 + CD4 + T cells polarizations in SLE, thus providing new insights into the mechanism of GC, CYC and HCQ in the treatment of SLE.